(untitled) (Scientific journal of the Fergana State University, 2024)
The article describes the emergence of human needs and interests in the information society, its important aspects, factors, purpose and essence. Research methods: Dialectics, analysis and synthesis, historicity, observation. Research results: During the study of the topic, the definitions of the concepts of needs and interests in the research of scientists and in dictionaries were compared. As a conclusion, a socio-philosophical analysis of conflicts in meeting the needs and interests of young people in the information space is given.